THE CORRELATION ANALYSIS BETWEEN BRAND EQUITY AND THE CUSTOMER DECISION BUYING AN AUTOMOTIVE PRODUCT - Fatimah Abdillah (The Management Journal of Binaniaga, 2017)
Some reasons have made the customer buying an automotive product, and one of it is a brand. Brand image is the power increasing the total sales of automotive products in Indonesia, so that more aspects affecting the power of the brand image need to be analyzed. This research is different with the previous one. It aims to recognize the effect of brand equity (brand awareness, brand association, quality perception, and brand loyalty) upon the consumer decision buying Toyota Kijang Innova which is one of the family premium high involvement products at Auto 2000 – Yasmin Branch in Bogor. This research has applied a descriptive quantitative approach refers to a survey upon 85 respondents as the customers of Auto 2000 Yasmin Branch in Bogor. Data analysis has implemented a multiple linear analysis using SPSS 16.0. The result of this research has identified partially that only the variable of brand loyalty has significantly affected the customer decision, though simultaneously all the dimensions of brand equity have affected the customer decision buying the product. Furthermore, the result can be used as a basic of marketing strategy regarding a high involvement product.Keywords: brand equity, loyalty, and buying decision.